1997
DOI: 10.3354/ame012123
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to heterotrophic bacterial and flagellate abundance in temperate rivers

Abstract: Thirty-one rivers of varying trophic status located in Ontario and Quebec, Canada, were sampled in order to determine the factors related to heterotrophic bacterial and flagellate abundance. Bacterial abundance ranged from 1.80 X 106 to 9.92 X 106 cells ml-' and flagellate abundance ranged from 1.18 X 103 to 17.4 X 103 cells ml-' There was a highly significant, positive relationship between bacterial abundance and both total phosphorus (R2 = 0.551 and chlorophyll a (R2 = 0.55). Bacterial abundance was not rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
1
12
2
Order By: Relevance
“…Previous studies have not generally observed a relationship between DOC concentrations and indicators of bacterial activity and growth (i.e., bacterial production and abundance) in rivers and estuaries (Findlay et al 1996, Basu & Pick 1997. This may be due, in part, to the continuum of reactivity within the DOC pool, because it is sometimes a small percentage of the DOC pool that supports the majority of bacterial carbon utilization (Wright & Hobbie 1965, Kirchman et al 1991, but see Amon & Benner 1996.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 98%
“…Previous studies have not generally observed a relationship between DOC concentrations and indicators of bacterial activity and growth (i.e., bacterial production and abundance) in rivers and estuaries (Findlay et al 1996, Basu & Pick 1997. This may be due, in part, to the continuum of reactivity within the DOC pool, because it is sometimes a small percentage of the DOC pool that supports the majority of bacterial carbon utilization (Wright & Hobbie 1965, Kirchman et al 1991, but see Amon & Benner 1996.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 98%
“…analyses have been published, expanding the originally very limited marine and freshwater databases to include rivers [14], salt lakes [15], hypertrophic ecosystems [16] and open ocean communities [17,18]. As a result, the link between bacterial abundance and phytoplankton biomass remains as one of the few undisputed patterns in aquatic microbial ecology.…”
Section: Achievements In Aquatic Microbial Ecologymentioning
confidence: 99%
“…Two studies applying a water quality model to Saar, Moselle and Rhine (Schöl et al, 1999;Schöl et al, 2002) show a low grazing pressure of metazooplankton on phytoplankton in former years. This low importance of metazooplankton in rivers was also found by Basu and Pick (1997), Karrasch et al (2001) and Weitere et al (2005).…”
Section: Metazooplanktonmentioning
confidence: 78%